Identification and expression analysis of duck interleukin-17D in Riemerella anatipestifer infection. (August 2016) - Diaz, Joyce Anne R.; Kim, Woo H.; Fernandez, Cherry P.; Jeong, Jipseol; Afrin, Fahmida; Lillehoj, Hyun S.; Kim, Suk; Kim, Sungwon; Dalloul, Rami A.; Min, Wongi
Abstract: Interleukin (IL)-17D is a proinflammatory cytokine with currently largely unknown biological functions. Here we provide the description of the sequence, bioactivity, and mRNA expression profile of duck IL-17D homologue. A full-length duck IL-17D (duIL-17D) cDNA with a 624-bp coding region was identified from the large intestine. duIL-17D shares approximately 94.7% identity with its chicken counterpart, which is also identified in this work. duIL-17D exhibits 62.6–68.4% and 52.1–53.1% identity with mammalian and piscine homologues. Recombinant duIL-17D promoted the expression of proinflammatory cytokines such as IL-6, IL-8, and IL-1β in duck embryo fibroblast cells. Very low levels of duIL-17D transcript were observed in healthy lymphoid tissues, including bursa, thymus, and spleen, while duIL-17D expression was relatively high in the heart. The duIL-17D expression profiles were examined in mitogen-stimulated splenic lymphocytes, as well as tissues affected by Riemerella anatipestifer infection. The levels of duIL-17D were mostly upregulated in mitogen-activated splenic lymphocytes but downregulated in the liver and spleen of R . anatipestifer -infected ducks. These results provide new insights into the roles of IL-17D in host protective immune responses to Riemerella infection, which can therefore lead to further studies of its biological functions in different disease models of ducks and other avian species. Highlights: Full-length duck IL-17D gene was identified in avian species. Recombinant IL-17D induced expression of proinflammatory cytokines IL-6, IL-8 and IL-1β. IL-17D transcript was generally upregulated in mitogen-activated splenic lymphocytes. Transcription of IL-17D gene, unlike IL-17A, is downregulated after Riemerella anatipestifer infection.